Sustainable ecological substrates for slope protection in harsh environments: A critical review of mechanisms, technologies, and future perspectives - Yong-qing Chen; Zi-yu Liu; Ming-xing Zheng; Wei Wang; Zhi Zhang; Da-wei Huang; Xin Kang (Ecological Engineering, 2026)

The precursor of ethylene, 1-aminocyclopropane-1-carboxylic acid, induces resistance against the root-knot nematode Meloidogyne graminicola in rice - Karen De Kock; Da Cao; Xing Xu; Kristof Demeestere; Dominique Van Der Straeten; Sven Mangelinckx; Tina Kyndt (Plant Science, 2026)

Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Potassium oxalate-activated bamboo charcoal: a green solution for constructing high-performance capacitive deionization electrodes for nitrate removal - Weilong Xiao; Rencheng Li; Ming Gao; Ran Li; Luwei Miao; Yufeng Da; Yang Bao; Ke Li; Tianqi Ao; Qiulin Yang; Xing Chen; Haiyan Mou; et al. (Desalination, 2026)

Surfactant-assisted hierarchical assembly of debranched starch nanoparticles: Insights into desolvation-driven molecular and crystalline ordering - Da-Hui Kim; Xing Zhou; Jong-Yea Kim (Carbohydrate Polymers, 2026)

Integrated geophysical investigation of a contaminated abandoned industrial site validated by borehole sample analysis: A case study in northeastern Shanghai, China - Shi-Jin Feng; Jin-Hui Shu; Xiao-Lei Zhang; Qi-Teng Zheng; Zhen-Xing Sun; Wen-Da Wang (Engineering Geology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The first cranium of Postschizotherium (Pliohyracidae, Hyracoidea) from the Lower Pleistocene of China - Lu-Da Xing; Xiao-Bing Wang; Martin Pickford; Yan-Jie Chen; Jiao Ma; Shu-Qiong Wang; Yi-Yang Liu; Shi-Qi Wang (Palaeoworld, 2026)

Experimental and analytical investigation on continuous two-span RC beams flexural strengthened with aluminum alloy bars - Xu Chen; Guohua Xing; Yakun Li; Jun Zhang; Da Luo; Zhaoqun Chang; Boquan Liu; Haonan Wang (Engineering Structures, 2026)

From half-cells to full-cells: across-scale comparative evaluation of lanthanum-based perovskites as high-performance anode materials for the oxygen evolution reaction - Blaž Toplak; Leon Müller; Ali Raza Khan; André Olean-Oliveira; Khuzaifa Yahuza Muhammad; Wang Feng; Raíssa Ribeiro Lima Machado; Da Xing; Mohammed-Ali Sheikh; Leander Kucklick; Ahammed Suhail Odungat; Adarsh Jain; et al. (Chemical Engineering Journal, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

The Combination of Sodium Tanshinone IIA Sulfonate and Mesenchymal Stem Cell-derived Exosomes Against Spinal Cord Injury via VEGF Pathway - Dan Luo; Lin Ma; Zhijian Pan; Ling Chen; Zhifeng Hu; Chaolun Liang; Zenglu Wang; Zhifeng Xiao; Dingkun Lin; Jinfeng Li; Da Guo; Xing Li (Molecular Neurobiology, 2026)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Interactive effects of soil characteristics and polymer types reveal patterns of denitrifying bacteria enrichment in the soil plastisphere - Ting Guo; Shunyin Huang; Xiangyi Jin; Mengyao Xing; Williamson Gustave; Yimin Cai; Da Ouyang; Mei Li; Yanjiang Cai; Haibo Zhang (Journal of Hazardous Materials, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Novel Pantoea brenneri CYD50–1 enables nitrogen-synergized enzymatic depolymerization of low-density polyethylene - Xiuya Xu; Shuai Liu; Jingli Pang; Yufan Fei; Mengyao Xing; Xiangyi Jin; Da Ouyang; Jing Li; Yating Luo; Haibo Zhang (Chemical Engineering Journal, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Pilot cultivation of a long-type variety in Pyropia suborbiculata (Bangiales, Rhodophyta) - Da-Hai Gao; Yan Zhang; Xing-Hong Yan (Journal of Applied Phycology, 2025)

Reanalysis-data-based approach to generate urban local weather data to support building energy design in a tropical climate - Xing Zheng; Naika Meili; Shuyang Li; Huanhuan Wang; Lei Xu; Zhen Han; Martín Mosteiro-Romero; Yi Wu; Da Yan; Dengkai Chi; Guanli Feng; Rudi Stouffs (Sustainable Cities and Society, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Target-oriented synthesis of yellow fluorescent nitrogen-doped carbon dots for intelligent and real-time visual detection of malachite green in fish - Xinru Liu; Yihao Zhang; Sineng Gao; Haoming Xing; Dingfeng Wang; Houwen Hu; Xiaoqing Qian; Da Chen (Analytica Chimica Acta, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Calcium oxide modification of phosphorus migration pathways during hydrogen reduction of high-phosphorus limonite - Lian-da Zhao; Mei-lin Shi; Xing-jian Deng; Jing-song Wang; Guang Wang; Qing-guo Xue; Hai-bin Zuo; Xue-feng She (Process Safety and Environmental Protection, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Regional transport characteristics of PM2.5 pollution events in Beijing during 2018–2021 - Dejia Yin; Qian Song; Yuanxi Guo; Yueqi Jiang; Zhaoxin Dong; Bin Zhao; Shuxiao Wang; Da Gao; Xing Chang; Haotian Zheng; Shengyue Li; Yunting Li; et al. (Journal of Environmental Sciences, 2025)

Characteristics of secondary microseisms generated in the Bohai Sea and their impact on seismic noise - Kang-Da Yin; Xiao-Gang Zhang; Xiao-Jun Li; Guo-Liang Mao; Xing-Xing Zhang; Xiao-Hui Jia (Applied Geophysics, 2025)

Assessment of high-position glacial valleys in Southeast Tibet, China: an integrated approach using remote sensing, UAV, field investigation, and numerical simulation - Congyan Ran; Shishu Zhang; Xinfu Xing; Haizhu Qu; Zhanglei Wu; Da Zheng; Zhenhui Pan; Maohong Yao; Kai Zhang (Natural Hazards, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

3D Seismic Data Reconstruction based on Weighted Fast Iterative Shrinkage Thresholding algorithm - Hua Zhang; Da-Xing Qiu; Zi-Fen Mo; Ya-Ju Hao; Zhao-Qi Wu; Meng-Xue Dai (Applied Geophysics, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Effect of exogenous abscisic acid on the formation and release of archeospores in Pyropia yezoensis - Li Zhang; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2025)

Bond-slip behavior of Aluminum Alloy (AA) bars for near-surface mounted (NSM) technique - Xu Chen; Guohua Xing; Da Luo; Yongjian Lu; Zhaoqun Chang; Enrique del Rey Castillo; Jason Ingham (Engineering Structures, 2025)

Pyrite geochemistry and its implications for ore formation in reduced copper skarn systems: A case study of the Saibo deposit, Northwest China - Qing-Fei Sun; Ju-Xing Tang; Shun-Da Li; Qiu-Ming Pei; Xin-Hao Sun; Chuan Chen; Ling-Ling Gao; Xiao-Fei Du; Jin-Ling Xie (Chemical Geology, 2025)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.

Centrifugated lateral flow assay strips based on dual-emission carbon dots modified with europium ions for ratiometric determination and on-site discrimination of tetracyclines in environment - Houwen Hu; Haoming Xing; Yihao Zhang; Xinru Liu; Sineng Gao; Linfan Wang; Tingting Li; Ting Zhang; Da Chen (Science of The Total Environment, 2024)

A novel photocurable polymeric solid–solid phase change material for intelligent temperature regulators - Meiqi Liu; Zhaowen Huang; Akbar Bashir; Yichi Zhang; Haixia Qian; Xing Ouyang; Yan Hu; Haibin Chen; Da-Zhu Chen (Chemical Engineering Journal, 2024)

Thyroxine regulates pig Sertoli cell line proliferation and maturation through the IKK/NFκB and p38 MAPK signaling pathways - Jing Li; Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Chun-Yan Bai; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Multi-dimensional signals coupling of simultaneous acquisition stripping current with laser-induced breakdown spectroscopy for accurate analysis of Cd(II) in coexisting Cu(II) - Yuan-Fan Yang; Zong-Yin Song; Zi-Hao Liu; Zhi-Wei Gao; Xin Cai; Cong-Cong Huang; Pang-Da Dai; Meng Yang; Pei-Hua Li; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Bonding-slip behaviour of steel-concrete interfaces in CFDST members with PBL ribs - Yan-Li Shi; Jia-Xing Ren; Jia-Hao Fan; Wen-Da Wang; Hai-Cui Wang (Engineering Structures, 2024)

Understanding the structural relation and electrochemical evolution between ZnGeP2 and ZnSiP2 twin phosphides for advanced Li-ion batteries - Wei Liang; Bin Chen; Da Li; Xuhao Liu; De Li; Xuan Tian; Panpan Zhang; Xing Lu; Yaqing Wei; Yong Chen (Chemical Engineering Journal, 2024)

Meticulously designed red emission carbon dots as efficient and stable luminescent species for rapid latent fingerprint recognition and light emitting diodes - Jianbo Cao; Rui Chen; Linfan Wang; Haoming Xing; Houwen Hu; Xiangdong Yang; Chenjie Gu; Siyuan Tang; Da Chen (Chemical Engineering Journal, 2024)

New formula of vegetation roughness height and Darcy–Weisbach friction factor in channel flow - Da-Qian Feng; Jing-Jing Fan; Wei-Jie Wang; Cheng-Xing Xia; Ang Li (Journal of Hydrology, 2024)

Variable climatic conditions dominate decreased wetland vulnerability on the Qinghai‒Tibet Plateau: Insights from the ecosystem pattern-process-function framework - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Lei Deng; Yuelu Wang; Da Lü; Yi Wang; Xing Wu (Journal of Cleaner Production, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Genesis of the Haidewula volcanic rock-hosted uranium deposit in the East Kunlun Orogen, northwestern China - Kai-Xing Wang; Kun-He Zhu; Jia-Wen Dai; Jian-Jun Yang; Xiao-Dong Liu; Michel Cuney; Chi-Da Yu; Jia Wu (Journal of Asian Earth Sciences, 2024)

Microcystin-RR promote lipid accumulation through CD36 mediated signal pathway and fatty acid uptake in HepG2 cells - Wenjuan Jia; Lin Zhong; Qingmiao Ren; Da Teng; Lei Gong; Haibin Dong; Jun Li; Chunxiao Wang; Yong-Xing He; Jun Yang (Environmental Research, 2024)

The earliest evidence for a microblade adaptation in the remote, high altitude regions of the Tibetan Plateau - Yingshuai Jin; Xiaoling Zhang; Shejiang Wang; Junyi Ge; Wei He; Wa Da; Yunyao Tan; Ziyi Yang; Christopher Morgan; Xing Gao (Science China Earth Sciences, 2024)

Binary Li/Na tungstates modified Mg6MnO8 as redox catalysts for enhanced performance of chemical looping oxidative dehydrogenation of ethane - Haitao Chen; Zifan Xing; Da Song; Xiang Yu; Yang Li; Fang He (Chemical Engineering Journal, 2024)

Mapping hydrothermal alteration zones with short wavelength infrared (SWIR) spectra and magnetic susceptibility at the Pulang porphyry Cu-Au deposit, Yunnan, SW China - Cheng-Biao Leng; Da-Zhao Wang; Hai-Jun Yu; Feng Tian; Xing-Chun Zhang (Mineralium Deposita, 2024)

Seasonal Variation of the Sea Surface Temperature Growth Rate of ENSO - Xinyi Xing; Xianghui Fang; Da Pang; Chaopeng Ji (Advances in Atmospheric Sciences, 2024)

Coupling urchin-like TiO2 nanospheres with nitrogen and sulfur co-doped graphene quantum dots for visible-light-induced degradation of toluene - Juntao Tang; Jiaxin Zhu; Luzhen Liu; Lin Xia; Zhiqiao He; Da Wang; Xing Xu; Shuang Song (Chemical Engineering Journal, 2024)

Inhibition of nucleotide metabolism with dual-template epitope imprinted nanoparticles for targeted HER2+ tumor therapy - Xing-Hui Ren; Lei Shi; Zi-Bo Ma; Da-Wei Wang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Chemical Engineering Journal, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Chlorogenic acid ameliorates the heat stress-induced impairment of porcine Sertoli cells by suppressing oxidative stress and apoptosis - Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Yu-Wei Yang; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Carbon and water relationships change nonlinearly along elevation gradient in the Qinghai Tibet Plateau - Yi Wang; Yihe Lü; Da Lü; Cong Wang; Xing Wu; Lichang Yin; Xiaofeng Wang (Journal of Hydrology, 2024)

Identification of antimicrobial peptide genes from transcriptomes in Mandarin fish (Siniperca chuatsi) and their response to infection with Aeromonas hydrophila - Jin-hua Gao; Jin-liang Zhao; Xiao-li Yao; Temesgen Tola; Jia Zheng; Wen-bo Xue; Da-wei Wang; Ying Xing (Fish & Shellfish Immunology, 2024)

Construction of fluorescent sensor array and three-dimensional microfluidic paper based analytical device for specific identification and visual determination of antibiotics in food - Tingting Li; Guoqiang Guo; Haoming Xing; Siyuan Tang; Houwen Hu; Linfan Wang; Xiaoqing Qian; Da Chen (Food Chemistry, 2023)

Transcriptome sequencing reveals the senescence mechanism of ethylene-insensitive cut Rhododendron flowers - Shi-da Xu; Fang Zheng; Xing-min Geng; Zhi-li Jiang; Ling-feng Mao; Jia-le Su (Postharvest Biology and Technology, 2023)

Effect of sulfuric acid pretreatment on flotation performance of calcite and fluorite - Ruofan Sun; Dingquan Xing; Jiushuai Deng; Da Jin; Shuai Ma; Jixing Liu; Guangsheng Li; Guanglin Qin; Xiao Liu (Minerals Engineering, 2023)

Effects of tillage patterns and stover mulching on N2O production, nitrogen cycling genes and microbial dynamics in black soil - Da-Cheng Hao; Xing-Yuan Su; Hong-Tu Xie; Xue-Lian Bao; Xu-Dong Zhang; Lian-Feng Wang (Journal of Environmental Management, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

Valorization of soybean plant wastes in preparation of N-doped biochar for catalytic ozonation of organic contaminants: Atrazine degradation performance and mechanistic considerations - Shiwen Dong; Xing Shen; Qingqing Guo; Haijun Cheng; Stefanos Giannakis; Zhiqiao He; Lizhang Wang; Da Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2023)

A novel approach to examining the optimal use of the cooling effect of water bodies in urban planning - Zehongyu Kang; Hua Liu; Yuxin Lu; Xinyu Yang; Xin Zhou; Jingjing An; Da Yan; Xing Jin; Xing Shi (Building and Environment, 2023)

Beyond iron-storage pool: functions of plant apoplastic iron during stress - Xing Xing Liu; Xiao Fang Zhu; Da Wei Xue; Shao Jian Zheng; Chong Wei Jin (Trends in Plant Science, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Spatiotemporal variations of the global compound heat wave and the drivers of its spatial heterogeneity - Lijun Jiang; Jiahua Zhang; Quan Liu; Xianglei Meng; Lamei Shi; Da Zhang; Mingming Xing (Journal of Cleaner Production, 2023)

Characterization of Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov., revealing the potential nitrogen fixation capacity of the order Marinilabiliales - Wen-Xing Yu; Qi-Yun Liang; Zong-Jun Du; Da-Shuai Mu (Frontiers in Marine Science, 2023)
Biological nitrogen fixation plays a crucial role in the marine nitrogen cycle, impacting global marine productivity and related carbon fluxes. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences.These two strains were isolated from the coastal sediment at Xiaoshi Island in Weihai, China. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences. It was revealed that strains D04 T and AAT T contain a set of nif gene clusters responsible for nitrogen fixation. Cell are yellow-colored, Gram-stain-negative, facultatively anaerobic, and rod-shaped bacteria. The optimal growth conditions for strain D04 T were found to be at 33 °C, pH 7.0, and in 2% (w/v) NaCl, while strain AAT T prefers growth conditions at 33 °C, pH 6.5, and in 3% (w/v) NaCl. The highest similarity of strains D04 T and AAT T was to Saccharicrinis fermentans NBRC 15936 T , with a similarity of 94.1% and 94.8%, respectively. The 16S rRNA gene sequence similarity between the two strains was 96.6%. These novel strains were found to represent new taxa of the Marinilabiliaceae family, and we propose the names Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov. with type strains D04 T (MCCC 1H00493 T = KCTC 92026 T ) and AAT T (MCCC 1H00485 T = KCTC 92028 T ), respectively. In this study, nitrogen fixation genes were predicted for 53 strains from the whole order Marinilabiliales and it was found that nitrogen fixation gene clusters were present in 26 strains. These gene clusters were found in every family in the order, highlighting that the presence of nitrogen-fixing gene clusters in the order is common. Nitrogen-fixing bacteria in sediments play an important role in various biogeochemical cycles. Thus, understanding the oceanic nitrogen cycle can provide insights into the energy flow of marine systems.

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

RNA-seq reveals the role of miR-223 in alleviating inflammation of bovine mammary epithelial cells - Yan-Xia Li; Peng Jiao; Xing-Ping Wang; Jin-Peng Wang; Fen Feng; Bin-Wu Bao; Yi-Wen Dong; Zhuo-Ma Luoreng; Da-Wei Wei (Research in Veterinary Science, 2023)

Beta diversity of urban spontaneous plants and its drivers in 9 major cities of Yunnan province, China - Zhiwen Gao; Yingji Pan; Peter M. Van Bodegom; Ellen Cieraad; Dingliang Xing; Yanyi Yang; Tiyuan Xia; Xinyi Luo; Kun Song; Liangjun Da; Dan Malkinson (Landscape and Urban Planning, 2023)

Activated cascade effect for dual-mode ratiometric and smartphone-assisted visual detection of curcumin and F− based on nitrogen-doped carbon dots - Siyuan Tang; Yiru Wang; Guoqiang Guo; Tingting Li; Haoming Xing; Houwen Hu; Xuan Leng; Chenjie Gu; Da Chen (Science of The Total Environment, 2023)

Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat - Jiahui Zhuo; Ke Wang; Ning Wang; Caihong Xing; Da Peng; Xinyu Wang; Ge Qu; Caiyun Kang; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Science, 2023)

Understanding gene regulation during the development of the sea cucumber Apostichopus japonicus using comparative transcriptomics - Fang Su; Shilin Liu; Lili Xing; Da Huo; Hongsheng Yang; Lina Sun (Frontiers in Marine Science, 2023)
Embryonic development, especially metamorphosis and settlement, has a major impact on the life history of marine invertebrates. Apostichopus japonicus is an economically important species of sea cucumber. In this study, we performed RNA sequencing on six key stages of A. japonicas development: fertilized eggs, blastula, gastrula, auricularia, doliolaria, and pentactula. A total of 32,353 genes were identified and annotated as a reference gene set for subsequent pairwise comparison analysis. After filtering out low-quality genes, the dynamic molecular responses to development were revealed by WGCNA. The results showed that of the 20 modules, genes in the blue, yellow, and darkslateblue modules were highly correlated with the gastrula, auricularia, and blastula stages, respectively. GO terms for “RNA” and “proteasome complex” were most significantly enriched in the blue module. In the darkslateblue and yellow module, receptors of signaling pathways and metabolic processes were significantly enriched, respectively. All DEGs were categorized into 34 terms, mainly associated with signal transduction and cellular immunity. The expression pattern of genes associated with adhesion, cell cycle, signal, transcription factor, extracellular matrix (ECM), and cytoskeleton was analyzed according to gene function. The results of this study facilitated a more comprehensive understanding of the molecular characteristics of sea cucumber embryonic development and will provide theoretical guidance for larva rearing in sea cucumber culture.

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

The involvement of an HMG-box gene in germ cell genesis in Pyropia haitanensis - Hong-Chang Ding; Long-Chen Tang; Da-Hai Gao; Xing-Hong Yan (Algal Research, 2023)

Synergistic nanowire-assisted electroporation and chlorination for inactivation of chlorine-resistant bacteria in drinking water systems via inducing cell pores for chlorine permeation - Ying-Wen Lu; Xiang-Xing Liang; Chen-Yang Wang; Da Chen; Hai Liu (Water Research, 2023)

Creep characteristics of thermally-stressed Beishan granite under triaxial compression - Jian-Feng Liu; Xing Luo; Gan Feng; Lu-Lin Zhou; Xing-Guo Yang; Gong-Da Lu (International Journal of Rock Mechanics and Mining Sciences, 2023)

Melatonin improves the removal and the reduction of Cr(VI) and alleviates the chromium toxicity by antioxidative machinery in Rhodobacter sphaeroides - Hao-Tian Mao; Lun-Xing Chen; Meng-Ying Zhang; Qiu-Yun Shi; Hong Xu; Da-Yan Zhang; Zhong-Wei Zhang; Ming Yuan; Shu Yuan; Huai-Yu Zhang; Yan-Qiu Su; Yang-Er Chen (Environmental Pollution, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Energy transfer mediated rapid and visual discrimination of tetracyclines and quercetin in food by using N, Cu Co-doped carbon dots - Tingting Li; Guoqiang Guo; Haoming Xing; Yiru Wang; Xinyu Luo; Linfan Wang; Chenjie Gu; Yafei Hou; Da Chen (Analytica Chimica Acta, 2023)

Regulation of reactive oxygen species on production, release, and early germination of archeospores in Pyropia yezoensis - Chao-Feng Teng; Da-Hai Gao; Hong-Chang Ding; Xing-Hong Yan (Algal Research, 2023)

Investigation on rheological and strength characteristics of cement-treated dredged materials - Feng Ji; Jia-xing Weng; Miao-miao Song; Da Yao; Dan Zhang (Marine Georesources & Geotechnology, 2022)

Robiginitalea marina sp. nov., isolated from coastal sediment - Xiao-Qi Xuan; Run-Yuan Mao; Wen-Xing Yu; Jing An; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Association of caffeine and caffeine metabolites with obesity among children and adolescents: National Health and Nutrition Examination Survey (NHANES) 2009–2014 - Linling Yu; Hong Mei; Da Shi; Xing Wang; Man Cheng; Lieyang Fan; Yang Xiao; Ruyi Liang; Bin Wang; Meng Yang; Weihong Chen (Environmental Science and Pollution Research, 2022)

Identification and expression profiling of HSP20 genes in Neoporphyra haitanensis - Ling-Na Peng; Lin-Bin Huang; Tian-Yu Gui; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2022)

Alternation of stromatolites and vertical burrows controlled by storm processes and sea-level changes in the middle Cambrian carbonates of central China - Bingchen Liu; Mingyue Dai; Yong’an Qi; Xiaofang Sun; Wei Zheng; Min Wang; Zhifeng Xing; Da Li; Yuchao Fan (Journal of Earth System Science, 2022)

Rapid visual detection of porcine reproductive and respiratory syndrome virus via recombinase polymerase amplification combined with a lateral flow dipstick - Xiao-Xiao Tian; Tao Wang; Xing-Yang Cui; Xin-Yi Huang; Yue Sun; Da-Song Xia; Yong-Bo Yang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2022)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

Microbiogenic thrombolites from the Cambrian Miaolingian Series of southern North China Craton - Xiaofang Sun; Mingyue Dai; Yong’an Qi; Bingchen Liu; Wei Zheng; Zhifeng Xing; Min Wang; Da Li; Yuchao Fan (Carbonates and Evaporites, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Systemic effect of dietary lipid levels and α-lipoic acid supplementation on nutritional metabolism in zebrafish (Danio rerio): focusing on the transcriptional level - Chen-cui Huang; Jian Sun; Hong Ji; Gen Kaneko; Xing-da Xie; Zhi-guang Chang; Wei Deng (Fish Physiology and Biochemistry, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Experimental study on the formation of landslide dams by fragmentary materials from successive rock slides - Hai-mei Liao; Xing-guo Yang; Gong-da Lu; Jian Tao; Jia-wen Zhou (Bulletin of Engineering Geology and the Environment, 2020)

Dynamic Elastic Modulus and Damping Ratio of Unsaturated Red Clay - Chang-xi Huang; Xing-hua Wang; Hao Zhou; Da-chao Qin (Geotechnical and Geological Engineering, 2020)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Fluids discrimination by ray-path elastic impedance inversion: A successful case from Sulige tight gas field - Da-Xing Wang; Hao-Fan Wang; Jin-Feng Ma; Yong-Gang Wang; Na Zhang; Lin Li (Applied Geophysics, 2019)

Systematic study of the quality and safety of chilled pork from wet markets, supermarkets, and online markets in China - Dong-wen Hu; Chen-xing Liu; Hong-bo Zhao; Da-xi Ren; Xiao-dong Zheng; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

Analysis on shear wave velocity structure of a gravel landslide based on dual-source surface wave method - Xing-qian Xu; Li-jun Su; Guang-da Zhang; Hong-hu Zhu (Landslides, 2017)

Biodegradation of sulfamethazine by an isolated thermophile–Geobacillus sp. S-07 - Lan-jia Pan; Xiao-da Tang; Chun-xing Li; Guang-wei Yu; Yin Wang (World Journal of Microbiology and Biotechnology, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Coherence estimation algorithm using Kendall’s concordance measurement on seismic data - Tao Yang; Jing-Huai Gao; Bing Zhang; Da-Xing Wang (Applied Geophysics, 2016)

Cytotoxic monoterpenoid indole alkaloids isolated from the barks of Voacanga africana Staph. - Hong-Mei Chen; Yu-Ting Yang; Hong-Xiang Li; Zhi-Xing Cao; Xiao-Mei Dan; Ling Mei; Da-Le Guo; Chuan-Xia Song; Yu Dai; Jia Hu; Yun Deng (Natural Product Research, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Impact of particulate and dissolved material on light absorption properties in a High-Altitude Lake in Tibet, China - Ciren Nima; Børge Hamre; Øyvind Frette; Svein Rune Erga; Yi-Chun Chen; Lu Zhao; Kai Sørensen; Marit Norli; Da-Ren Lu; Qian-Guo Xing; Yao-Ming Ma; Norsang Gelsor; et al. (Hydrobiologia, 2016)

Calcitonin Gene-Related Peptide-Induced Calcium Alginate Gel Combined with Adipose-Derived Stem Cells Differentiating to Osteoblasts - Chang-zhi Huang; Xiao-ning Yang; Da-cheng Liu; Yi-gong Sun; Xing-ming Dai (Cell Biochemistry and Biophysics, 2015)
Calcitonin gene-related peptide (CGRP) has been confirmed with induction osteoblastic differentiation, but if it can make the three-dimensional culture of adipose-derived stem cells (ADSCs) to the osteoblastic differentiation, thus constructing tissue-engineered bone rare reports. To investigate the feasibility of exogenous CGRP-induced calcium alginate gel combined with ADSCs from rabbits in three-dimensional condition to construct tissue-engineered bone. ADSCs were obtained by collagenase I digestion of the subcutaneous adipose tissue of inguinal region of New Zealand rabbits. At the third passage, cells were mixed with sodium alginate to prepare calcium alginate gel, and the cells were assigned into two-group cultivates in 24 orifice plates. ADSCs in the control group were treated with DMEM/F-12 medium supplemented with 10 −2 mol/L β-glycerophosphate sodium, 10 −7 mol/L dexamethasone, 50 mg/L ascorbic acid, 0.1 % volume fraction of fetal bovine serum. ADSCs in the experimental group were incubated with the same medium as above, and in addition 1.5 µg/L CGRP was added. The cells proliferation and the mRNA expressions of collagen I and osteocalcin were detected by MTT and RT-PCR assays, respectively and alkaline phosphatase(ALP)and calcium concentration at different induction time were detected. The cell proliferation curves were S shaped. The OD values of experimental group were higher than those of control group at 1, 3, 5, 7, 14, and 21 days after osteogenic induction ( P < 0.05). ALP and alizarin red stains of ADSCs were all positive, but golden round nodes became bigger and more in the experimental group compared with the control group after 2 weeks. At 7 and 14 days, collagen I and osteocalcin mRNA expression were greater in the experimental group than the control group. ALP and calcium concentration of experimental group were higher than that of control group at 1, 2, 3, 4 weeks after osteogenic induction ( P < 0.05). Thus, these results show that the CGRP-induced ADSCs combined with calcium alginate gel to osteoblasts differentiation.

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

The “valley economy” model of regional development: A case study of mountain areas in Beijing, northern China - Chun-la Liu; Ming-xing Chen; Zhi-peng Tang; Wei-dong Liu; Da-dao Lu; Yi-feng Zhang (Journal of Mountain Science, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Quantitative assessment of the effect of ABCA1 gene polymorphism on the risk of Alzheimer’s disease - Xiao-Feng Wang; Yuan-Wu Cao; Zhen-Zhou Feng; Da Fu; Yu-Shui Ma; Feng Zhang; Xiao-Xing Jiang; Yun-Chao Shao (Molecular Biology Reports, 2013)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Pseudonocardia yuanmoensis sp. nov., a novel actinobacterium isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Da-Qiao Wei; En-Min Zhou; Xia Tang; Juan Cheng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

YAP accelerates Aβ25–35-induced apoptosis through upregulation of Bax expression by interaction with p73 - Heng Zhang; Shengnan Wu; Da Xing (Apoptosis, 2011)

Molecular cloning and characterization of Izumo1 gene from sheep and cashmere goat reveal alternative splicing - Wan-Jin Xing; Bao-Da Han; Qi Wu; Li Zhao; Xiao-Hong Bao; Shorgan Bou (Molecular Biology Reports, 2011)

Genes required for the functions of olfactory AWA neuron regulate the longevity of Caenorhabditis elegans in an insulin/IGF signaling-dependent fashion - Lu-Lu Shen; Min Du; Xing-Feng Lin; Ting Cai; Da-Yong Wang (Neuroscience Bulletin, 2010)

Isolation and characterization of microsatellite markers for Glytothorax zanaensis - Shao-Ping Liu; Xi-Ping Yuan; Deng-Qiang Wang; Xing-Jian Yue; Yan Zhang; Ke Wang; Xin-Bin Duan; Da-Qing Chen (Conservation Genetics Resources, 2009)

Research progress in transient receptor potential vanilloid 1 of sensory nervous system - Da-Lu Liu; Wen-Ting Wang; Jun-Ling Xing; San-Jue Hu (Neuroscience Bulletin, 2009)

BimL displacing Bcl-xL promotes Bax translocation during TNFα-induced apoptosis - Lan Zhang; Da Xing; Miaojuan Chen (Apoptosis, 2008)

Implication of reactive oxygen species and mitochondrial dysfunction in the early stages of plant programmed cell death induced by ultraviolet-C overexposure - Caiji Gao; Da Xing; Lingling Li; Lingrui Zhang (Planta, 2008)

Real-time monitoring full length bid interacting with Bax during TNF-α-induced apoptosis - Yihui Pei; Da Xing; Xuejuan Gao; Lei Liu; Tongsheng Chen (Apoptosis, 2007)

Some key issues on the application of satellite remote sensing to mining areas - Pei-jun Du; Xing-dong Zhou; Da-zhi Guo (Chinese Geographical Science, 2003)

Study on the subsiding land extraction from landsat TM image supported by GIS and domain knowledge - Xing-dong Zhou; Pei-jun Du; Da-zhi Guo (Chinese Geographical Science, 2003)

Both spillover and light absorption cross-section changes are involved in the regulation of excitation energy distribution between the two photosystems during state transitions in wheat leaf - Xin-Xing Tan; Da-Quan Xu; Yun-Kang Shen (Photosynthesis Research, 1998)